Elaboração de pernil curado de coelho com reduzido teor de sódio - Pedro, Douglas (2021)
Cured meat products are usually produced with high salt levels to guarantee the microbiological quality of the final product and to improve the sensory characteristics. This study aimed to produce low-sodium dry-cured rabbit leg, and to evaluate the effect of this reformulation on the physicochemical and sensory characteristics. The legs were made with a reduction or replacement of 50% of NaCl by KCl and the addition of monosodium glutamate (MG). After salting, the legs were placed in a ripening chamber under the following temperature and relative humidity (RH) conditions: 2 ± 1 °C and 90 ± 5% RH from day 1 to 7; and 12 ± 1 °C and 70 ± 5% RH from day 8 to 28 of storage. The sodium reformulation had no major impact on aw, pH, and weight loss of the samples during processing. All treatments showed high protein (> 30%) and low fat (<6.0%) levels. The amino acid score was above 1.0 for all essential amino acids. Oleic acid was the main fatty acid (FA), representing almost 1/3 of the total fatty acids. All reformulated treatments presented a sodium reduction close to 45%, and the formulations made with the addition of KCl showed a healthy Na/K ratio. A lower saltiness perception was reported by consumers in the sorting task for the samples with a 50% salt reduction. The formulations containing KCl showed lower flavor and overall acceptance scores (P <0.05), and were characterized in the CATA test by the attributes "astringent flavor", "bitter taste" and "metallic taste". Although MG led to an increase in the saltiness of the formulations made with a 50% salt reduction, it was not effective to suppress all the sensory defects caused by the addition of KCl. The changes observed in TBARS values, pH, and redox potential throughout 90 days of storage at 20 ºC demonstrated that the sodium reformulation did not affect the oxidative stability of the product.